Anmeldelser - Buhl-Mortensen, Kristian (Danish Yearbook of Musicology, 1993)
Review of: Catalogue of the Rischel and Birket-Smith Collection of Guitar Music in The Royal Library of Copenhagen. Compiled by Jytte Torpp Larsson, edited by Peter Danner. Editions Orphée. Columbus, Ohio 1989.